Retrospective assessment of macrophytic communities in southern Lake Garda (Italy) from in situ and MIVIS (Multispectral Infrared and Visible Imaging Spectrometer) data - Claudia Giardino; Alessandro Oggioni; Rossano Bolpagni; Mariano Bresciani; Federica Braga (Journal of Limnology, 2012)
In situ and hyperspectral MIVIS (Multispectral Infrared and Visible Imaging Spectrometer) images acquired over a period of 13 years are used to assess changes in macrophyte colonization patterns in the coastal zones of the Sirmione Peninsula in the southern part of Lake Garda (Italy). In situ data (abundance, cover density and diversity of macrophyte communities) and MIVIS-derived maps of colonized substrates are analyzed by considering the variability of the main hydrological and physicochemical variables in order to indicate the main factors that explain the spatiotemporal variability of macrophyte communities. The results show a considerable modification in terms of macrophyte structural complexity and colonized areas. Almost 98% of macrophyte meadows (in particular communities with a density of over 70%) are lost and subsequently replaced by moderate to extremely rare communities with density from 10% to 40%. Well-established submerged macrophytes are replaced by de-structured communities characterized by moderate to scarce density: on average lower than 30%. The study indicates that macrophyte distribution along the littoral zone of the Sirmione Peninsula is certainly linked to water transparency and water level fluctuation. The results also indicate that the worsening of eutrophication may be associated with the gradual disappearance of macrophyte meadows, but may also be accelerated by herbivorous aquatic birds grazing there. Lastly, the increasing frequency and number of catamaran tours could be considered a threat for the stability of these valuable communities.